On the accuracy of the ray-tracing algorithms based on various sound receiver models - Xiangyang, Zeng; Ke'an, Chen; Jincai, Sun (Applied acoustics, 2003)
In this paper, the effect of sound ray detection on the accuracy of sound field simulation by using the ray-tracing technique has been discussed. The current methods to define the receiver size have been briefly described. Then a new equation for the computation of the size of a receiver has been proposed and it has considered such factors as the size of the room, the number of initial rays and the distance from source to receiver. The corresponding algorithm has been compared with two other algorithms that are based on different receiver models. It can be concluded from the computed and measured results that the new model is applicable for more extensive situations.